Intraoperative test stimulation of the subthalamic nucleus aids postoperative programming of chronic stimulation settings in Parkinson's disease. (August 2019) - Geraedts, V.J.; van Ham, R.A.P.; Marinus, J.; van Hilten, J.J.; Mosch, A.; Hoffmann, C.F.E.; van der Gaag, N.A.; Contarino, M.F.
Abstract: Background: It is unknown whether intraoperative testing during awake Deep Brain Stimulation (DBS) of the subthalamic nucleus (STN) can be used to postoperatively identify the best settings for chronic stimulation. Objective: To determine whether intraoperative test stimulation is indicative of postoperative stimulation results. Methods: Records of consecutive Parkinson's Disease patients who received STN DBS between September 2012 and December 2017 were retrospectively analyzed. The best depth identified after intraoperative stimulation via the microelectrode's stimulation tip was compared with the depth of the contact selected for chronic stimulation after a standard monopolar contact review. Moreover, thresholds for induction of clinical effects (optimal improvement of rigidity and induction of side-effects) were compared between stimulation at the postoperatively selected contact and at the corresponding intraoperative depth. Results: Records of 119 patients were analyzed (mean (SD) age 60.5 (6.5) years, 31.9% female, 238 STNs). In 75% of cases, the postoperatively selected contact corresponded with the intraoperative depth with the largest therapeutic window or was immediately dorsal to it. Higher stimulation intensities were required postoperatively than intraoperatively to relieve rigidity (p = 0.002) and induce capsular side-effects (p = 0.016). Conclusion: In the majority of cases, the postoperative contact for chronic stimulation was at a similar level or immediately dorsal with respect to the identified best intraoperative depth. Postoperatively, relief of rigidity and induction of capsular side-effects occur at higher stimulation intensities than during intraoperative test stimulation. Highlights: Intraoperative testing is suggestive of the best location for chronic stimulation. Higher stimulation intensity is required postoperatively for induction of effects. Our results may improve the efficiency of achieving optimal DBS settings.